Water literacy and citizenship: education for sustainable domestic water use in the East Midlands - Wood, Georgina Victoria (2014)
In Britain, projected population rise and climate change threaten future water availability. UK water companies run education programmes to encourage more efficient usage, but these tend to focus on primary schools and adults, missing the opportunity to engage secondary school pupils as the next generation of homeowners and bill payers. Educational interventions also traditionally follow the theory of rational choice, envisaging learners as able to change their attitudes and behaviours in accordance with newly acquired information. Sociological research on social practices and ordinary consumption, however, sees water as playing an inconspicuous role in daily domestic activities. Technological infrastructure and prevalent social norms mould behaviour and limit the ability of water users to alter their consumption. This interdisciplinary thesis attempts to break the impasse between works from educational and sociological perspectives, using the theoretical lens of water citizenship. A review of current water education provision in the East Midlands region was undertaken, and a school-based study involving questionnaires, focus groups and exploratory lessons around water. The young people involved in the study tended to show ambivalence towards water conservation, despite general pro-environmental motivations. While some teenagers perceived they were ‘doing their bit’ for the environment, this tended to be limited to accepting and invoking ‘water saving tips’, and many teenagers eschewed water conservation altogether. These findings indicate that innovative educational programmes are needed to raise the standard of water literacy in the UK. This thesis argues firstly for making water use more ‘visible’ in daily activities, by deconstructing the routines and habits that use water, and by recognising the influences that social norms exert on water use. Secondly, it argues that educational initiatives for water literacy could develop young people’s sense of citizenship and responsibility towards water resources by connecting personal actions to impacts at local, national and global scales.